The Effect of Adversity Quotient and Self-Efficacy on The Ability of Understanding Mathematical Concepts of Vocational High School Students - Rahmayanti, Wulan; Marlena, Leni (Tematik : Jurnal Konten Pendidikan Matematika, 2025)
This study aims to see whether there is an influence of AQ and SE, both partially and simultaneously on the ability to understand mathematical concepts in vocational students. The research method used is quantitative research with a population of all grade XI students, and a sample of 95 students. Data were collected through questionnaires to measure AQ and SE variables, as well as five essay questions on statistics material to measure the ability to understand mathematical concepts. The analysis results showed that the significance values of AQ and SE were 0.041(<0.05) and 0.858(>0.05). This means that partially only AQ has an influence on students' mathematical concept understanding ability. However, the results of the F test showed a significance value of 0.029(<0.05), so that simultaneously AQ and SE affect the ability, with a contribution of 5.4%.